ANALISIS ITEM SOAL DENGAN MENGGUNAKAN RASCH MODEL SEBAGAI UKURAN KUALITAS MADRASAH IBTIDAIYAH PADA MATA PELAJARAN IPA - Lilla Septiliana (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2023)
Comprehensive Assessment as an Effort to Improve Evaluation Quality to Measure the Level of Difficulty of Questions, Item Fit, and Possibility of Item Bias. This exploratory and descriptive research aims to retro-fit the test items and student answer data in the 2nd semester of the Natural Sciences Test for the 2022/2023 school year. The research findings include the following: 1. The difficulty level of the questions was identified in item S14 with a measurement value of +2.82, and only 25 students answered correctly. 2. Item fit meets the criteria except for item S14, which indicates an answer outside the Outfit Trust limits. However, the mean clothing values and spot size correlations are still in agreement. 3. Detected bias in question item S13, with a probability value of 0.02, which is below the 5% limit (0.05).